2014
DOI: 10.5021/ad.2014.26.3.395
|View full text |Cite
|
Sign up to set email alerts
|

Sebaceous Carcinoma of the Suprapubic Area in a Liver Transplant Recipient

Abstract: Sebaceous carcinoma is a very rare and potentially aggressive carcinoma originating from the epithelial lining of the sebaceous gland. More than 70% of all cases are in the head and neck region, especially the periorbita; therefore, they are classified into ocular and extraocular sebaceous carcinoma. The reported risk factors are advanced age, male sex, previous irradiation, and genetic predisposition for Muir-Torre syndrome. The current case is of sebaceous carcinoma found in the suprapubic area of a 67-year-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…More recently, external beam radiation therapy (XRT) has been used successfully as adjuvant therapy after surgical excision in extraocular SC with lymph node involvement, extensive local invasion, or for recurrent disease. 19,35,36,[47][48][49][50][51][52][53] Of note, the majority of reported cases lack crucial information, including margin status after excision and location of radiation site. See Table 1 for a summary of 15 reported extraocular SC cases using XRT.…”
Section: Surgical Treatmentmentioning
confidence: 95%
“…More recently, external beam radiation therapy (XRT) has been used successfully as adjuvant therapy after surgical excision in extraocular SC with lymph node involvement, extensive local invasion, or for recurrent disease. 19,35,36,[47][48][49][50][51][52][53] Of note, the majority of reported cases lack crucial information, including margin status after excision and location of radiation site. See Table 1 for a summary of 15 reported extraocular SC cases using XRT.…”
Section: Surgical Treatmentmentioning
confidence: 95%
“…Furthermore, the lesion occurred in the suprapubic or lower abdominal region; this is uncharacteristic for sebaceous adenomas, which typically arise in the head and neck region. Interestingly, a previous report identified a sebaceous neoplasm after solid-organ transplantation in the same suprapubic location 11 …”
Section: Discussionmentioning
confidence: 97%
“…Reports of sebaceous neoplasms with mixed adenoma and carcinoma features arising in transplant recipients suggest the possibility of a sebaceous adenoma–sebaceous carcinoma neoplastic sequence 11, 12. Histopathologic analysis of these lesions identified focal regions of infiltrative growth and cellular atypia within an otherwise mostly well-differentiated collection of sebaceous gland-forming sebocytes 11, 12. Although histopathologic analysis of our individual's lesion showed no evidence of sebaceous carcinoma, treatment with complete excision and close follow-up for recurrence is reasonable because the potential for malignant growth exists.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the iatrogenic factors, azathioprine has been postulated to contribute to the selection of cells bearing DNA MMR deficits, evading its cytotoxic effects [35]: in fact, there is evidence suggesting that immunosuppressive drugs, most plausibly azathioprine, could determine the selection of a mutator phenotype predisposing to the development of sebaceous neoplasms [21]. Cyclosporine and tacrolimus are calcineurin inhibitors and have been hypothesised to increase tumour growth through the increase of transforming growth factor (TGF)-β and interleukin-6 [24,36]. Maluccio et al found that tacrolimus has a dose-dependent effect on tumour progression and TGF-β1 expression in mice [37].…”
Section: The Role Of Immunosuppressive Therapymentioning
confidence: 99%
“…Along the same lines, it is also known that the occurrence of sebaceous tumours is modulated by specific type of immunosuppressive drugs [19,20], and some primary and secondary immunodepressive conditions are associated to an increased incidence of rare sebaceous tumours [21], showing MSI and IHC aberrations. In this regard, beyond the direct pathogenic effect of oncogenic viruses [13], a role for immunosuppressive therapies [18,[22][23][24], genetic aberrations [22,25] and MLH1 hypermethylation [26] have been hypothesised. Regarding this latter phenomenon, it is known that some MSI-high cancers are due to aberrant MLH1 gene promoter methylation, a somatic event leading to LS/MTS phenocopies [26,27].…”
Section: Introductionmentioning
confidence: 99%